The Effect of Audit Tenure, KAP Reputation, and The COVID-19 Pandemic on Audit Quality - Awaloedin, Dipa Teruna; Effendy, Siti Nur Aisyah; Meini, Zumratul; Cik, Ahmad (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This study empirically aims to determine the effect of tenure audits, public accountants' reputation, and the COVID-19 pandemic on audit quality in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This research is quantitative, with a population of 52 companies, and sampling techniques were carried out using the purposive sampling method to obtain a sample of 32 companies. The results showed that audit tenure has a positive effect on audit quality, meaning that the longer the audit tenure, it will encourage the creation of understanding for an auditor of the company being audited. Furthermore, the reputation of KAP negatively affects audit quality; this shows that non-Big Four KAPs have no less good performance so that they can improve audit quality. The COVID-19 pandemic has negatively affected audit quality, which means that weak economic conditions have provided obstacles for the Company and KAP, causing audit quality to decline.